Determination of Cadmium and Trace Elements in Some Spices Cultivated in Turkey - OZKUTLU, FARUK (Asian Journal of Chemistry, 2010)
In recent years, there has been a growing interest in monitoring trace element and cadmium contents of spices and herbs. Some spices widely cultivated and consumed in Turkey were monitored as to their trace element and heavy metal contents including cadmium, iron, copper, manganese and zinc by ICP-AES. Samples of cumin (Cuminum cyminum L.), linseed (Linum usitatissimum L.), aniseed (Pimpinella anisum L.), fenugreek (Trigonella foenumgraceum L.), coriander (Coriandrum sativum L.), fennel (Foeniculum vulgare Mill.), poppy (Papaver somniferum L.) and tarragon (Artemisia dracanculus L.) were subjected to chemical analysis. Cadmium was not detectable in any samples of poppy seed. Linseed contained the highest amount of cadmium (128 μg kg-1) in all plant samples while fenugreek contained the least (7 μg kg-1). The level of copper in the samples varied from 6.0 to 17 mg kg-1 with the highest value was in tarragon. Content of iron ranged from 29 mg kg-1 in poppy seed to 129 mg kg-1 in cumin. The tarragon sample occurred as the richest (42 mg kg-1) in manganese content whereby the lowest manganese level was detected in fenugreek (8 mg kg-1). Zinc concentrations of the plant samples ranged between 11 and 28 mg kg-1 with linseed containing the highest. The results of the present study revealed that trace metal contents of some selected spices commonly cultivated in Turkey were within the low range.